Enhanced collagenogenesis on three-dimensionally printed titanium surfaces by human gingival fibroblasts: An in vitro study - de Toledo Stuani, Vitor; da Silva, Isabela Sanches Pompeo; do Prado Manfredi, Gustavo Gonçalves; Cassiano, Fernanda Balestrero; Alamo, Larissa; Corrêa, Ligia Espoliar; Shibli, Jamil Awad; de Souza Costa, Carlos Alberto [UNESP]; Soares, Diana Gabriela (American Vacuum Society, 2025)
The lack of cementum in peri-implant tissues leads to a deficiency in anchorage points for gingival collagen fibers. This arrangement is linked to reduced protective capabilities compared to teeth. Therefore, there is a pressing need to develop surfaces that optimize the interaction between soft tissue and implants. 3D-printed titanium disks (Ti3DP), machined disks (TiMC), and glass coverslips (GS) were seeded with human gingival fibroblasts. These specimens underwent mechanical characterization via roughness and wettability assays. Biological characterization included assessments of cellular viability (live/dead), adhesion and spreading (F-actin), cell count (DAPI), cellular metabolism (Alamar blue), adhesive strength, and soluble collagen and total protein quantification up to 14 days. Data analysis employed Student's t-test and ANOVA post-hoc Tukey test (α = 0.05). The group TiMC exhibited higher hydrophilicity and lower roughness compared to Ti3DP. All groups demonstrated cellular viability throughout the study period. Adhesive strength did not significantly differ among groups; however, cell count was higher in TiMC and GS after one day of cell seeding in comparison to Ti3DP. Morphologically, GS and TiMC displayed more fusiform cells with a uniform distribution, while Ti3DP showed smaller, irregular cells with multiple lamellipodia and filopodia. Additionally, statistically superior collagen and total protein deposition was observed in Ti3DP (p < 0.01). The 3D-printed titanium surface allowed human gingival fibroblasts to adhere to it, leading to a 3D cytoskeleton morphology that culminated in increased collagen expression. Therefore, these 3D-printed devices present a promising avenue for producing transmucosal components due to their increase in collagen production.